PENGARUH BERAT PATI DAN VOLUME PLASTICIZER GLISEROL TERHADAP KARAKTERISTIK FILM BIOPLASTIK PATI KENTANG - Afiifah Radhiyatullah, Novita Indriani, M. Hendra S. Ginting (Jurnal Teknik Kimia USU, 2015)
Bioplastics are plastics which can be degraded by microorganisms and is made from renewable materials. Plastic film is made from potato starch (contain of starch that founded in potatoes is 22-28%), glycerol as a plasticizer and acetic acid as a catalyst. The purpose of this reasearch is to determine glycerol variation and starch weight effect on the characteristics of potato starch plastic films. Manufacture of plastic films use blending starch method with potato starch weight variations (10 g, 15 g and 20 g) and glycerol volume variations (0 ml, 1 ml, 2 ml and 3 ml). Bioplastic analysis are FTIR test, tensile strength that is supported by SEM analysis. The results obtained in the FTIR analysis does not form a new cluster on potato starch plastic film, neither on the plastic film with or without glycerol. FTIR results obtained in two plastic film are the change of OH, C = C, and CH groups strain. The strain value of OH group on potato starch is 3579.88 cm-1 turned into 2978.09 cm-1 for plastic film without glycerol while the plastic film with glycerol to be 3541.31 cm -1 and 2970.38 cm-1. C = C group is 1635.64 cm-1 turned to 1697.36 cm -1 and 1697.36 cm -1. As for CH group is 2873.79 cm -1 turned to 2877.79 cm -1 and 2870.08 cm -1. And tensile strength of plastic film decreased with increasing glycerol volume. Maximum tensile strength of plastic film occurs when potato starch weight is 10 g and glycerol volume is 0 ml is 9.397 MPa. While SEM results obtained confirm on tensile strength plastic film, where there are voids, indentations and insoluble starch clump starch that can affect the value of tensile strength plastic film.